The importance of growing up: juvenile environment influences dispersal of individuals and their neighbours. (18th November 2018) - Endriss, Stacy B.; Vahsen, Megan L.; Bitume, Ellyn V.; Grey Monroe, J.; Turner, Kathryn G.; Norton, Andrew P.; Hufbauer, Ruth A.
Abstract: Dispersal is a key ecological process that is strongly influenced by both phenotype and environment. Here, we show that juvenile environment influences dispersal not only by shaping individual phenotypes, but also by changing the phenotypes of neighbouring conspecifics, which influence how individuals disperse. We used a model system ( Tribolium castaneum, red flour beetles) to test how the past environment of dispersing individuals and their neighbours influences how they disperse in their current environment. We found that individuals dispersed especially far when exposed to a poor environment as adults if their phenotype, or even one‐third of their neighbours' phenotypes, were shaped by a poor environment as juveniles. Juvenile environment therefore shapes dispersal both directly, by influencing phenotype, as well as indirectly, by influencing the external social environment. Thus, the juvenile environment of even a minority of individuals in a group can influence the dispersal of the entire group.